Assessment of Raftlin and blood count parameters in otosclerosis - Erdem, Duygu; Eliçora, Sultan Şevik; Güven, Berrak; Baklaci, Deniz (Frontiers in Neurology, 2025)
ObjectiveAlthough otosclerosis is a common disease, its etiology has not yet been clearly elucidated. One of the factors recently implicated in its pathogenesis is chronic inflammation. Blood count parameters are known as classical inflammatory markers in several diseases. Raftlin is also a novel biomarker of inflammation. The present study aimed to investigate Raftlin levels and blood count parameters in otosclerosis.MethodsThe study included 50 otosclerosis patients and 50 healthy volunteers. Serum Raftlin levels and white blood cell, neutrophil, lymphocyte and platelet counts, neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), and mean platelet volume (MPV) were measured in otosclerosis patients and compared with the controls.ResultsWhite blood cell and neutrophil counts and NLR were statistically higher in otosclerosis patients than in the control group (p < 0.001). There was no statistically significant difference between the control and patient groups in lymphocyte and platelet counts, and MPV and PLR values. The Raftlin level was also statistically significantly higher in otosclerosis patients than in the control group (p = 0.001).ConclusionThe Raftlin level and NLR value were significantly higher in otosclerotic patients than in healthy controls, supporting the presence of an inflammatory etiology for otosclerosis. Our study is the first in the literature to investigate the relationship between otosclerosis and Raftlin with known inflammatory markers.